Digital Classical Philology Ancient Greek and Latin in the Digital Revolution - Berti, Monica (De Gruyter, 2019)
This book describes the state of the art of digital philology with a focus on ancient Greek and Latin. It addresses problems such as accessibility of information about Greek and Latin sources, data entry, collection and analysis of Classical texts and describes the fundamental role of libraries in building digital catalogs and developing machine-readable citation systems.
Description based on print version record.
KU Select 2018: HSS Frontlist Books
Keywords: Language Arts & Disciplines / Library & Information Science; Language arts; Electronic books